THE RELATIONSHIP OF SERVICE QUALITY WITH CUSTOMER LOYALTY AT AMARIS HOTEL BENGKULU CITY - Marita Vriscilla Putri; Karona Cahya Susena; Siti Hanila (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
The purpose of this study was to determine the relationship between service quality and customer loyalty at Amaris Hotel, Bengkulu City. The sample in this study amounted to 75 people Amaris Hotel Bengkulu customers who came to stay at Amaris Hotel, Bengkulu City. Data collection using questionnaires and analytical methods used are Spearman rank correlation and hypothesis testing. The results of rank spearman correlation show a very strong relationship between service and customer loyalty of Amaris City of Bengkulu City with a correlation value of 0.853. This shows that there is a very strong correlation between service and customer loyalty at Amaris Hotel, Bengkulu City. The better service will increase the level of customer loyalty at Amaris Hotel, Bengkulu City. Hypothesis testing results of tcount are greater than t table (13,974> 1,666) meaning that service has a significant relationship with customer loyalty at Amaris Hotel, Bengkulu City. This explains that there is a close relationship between service and customer loyalty, if the services provided by employees of the Amaris Hotel in the City of Bengkulu, visitors will feel satisfied and stay loyal to stay at Amaris Hotel, Bengkulu City.